The Relationship between Nurses' Therapeutic Communication and the Level of Satisfaction of Outpatient Poly Patients at the South Sanggata Health Center, East Kutai Regency n 2023 - Neng Sofiah; Ratanto; Abd Kadir (Formosa Journal of Science and Technology, 2023)
Therapeutic communication is both verbal and non-verbal communication applied by nurses to accelerate patient healing. A nurse's good communication skills have a direct impact on patient satisfaction, that is, the feelings that arise as a result of the performance of health services obtained after being compared to what he expected. Determine the relationship between nurses' therapeutic communication and the The results of the Chi Square statistical test of the SPSS 25 program in table 4.7 obtained a P-value value of < α where the P-value (0.003) < α (0.05) so that it can be concluded that there is a significant relationship between nurse therapeutic communication and patient satisfaction at the South Sanggatta Health Center inpatient poly, East Kutai Regency in 2023. There is a significant relationship between nurses' therapeutic communication and patient satisfaction at the South Sanggatta Health Center in East Kutai Regency in 2023.